MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA DENGAN INTEGRASI STEAM PADA SISWA SMP 27 MAKASSAR - Jeranah; Asdar; Rezki Novianti (Almeera Education, 2024)
Critical thinking skills are one of the key competencies that students must possess to face future challenges. In the context of mathematics learning at SMP Negeri 27 Makassar, mathematical critical thinking skills are essential and need to be developed to support the advancement of knowledge in the era of globalization. However, mathematics learning often does not fully focus on the development of higher-order thinking skills. A learning approach that integrates STEAM (Science, Technology, Engineering, Art, and Mathematics) can be a solution, as it allows students to understand and apply mathematical concepts in real-world situations. The integration of science, technology, engineering, art, and mathematics elements in learning creates a more creative, holistic, and relevant learning experience. This study aims to analyze how the STEAM approach can help students at SMP Negeri 27 Makassar see the connections between scientific fields and apply them to solve real-world problems, thereby enhancing their critical thinking skills. This research uses a literature review method. The analysis results show that the implementation of STEAM-based learning at SMP Negeri 27 Makassar is effective in improving students' critical thinking skills. The integration of the STEAM approach in mathematics learning makes a significant contribution to the development of critical thinking skills, preparing students to face increasingly complex and dynamic global challenges.